MultiSCED: A tool for (meta-)analyzing single-case experimental data with multilevel modeling - Declercq, Lies; Cools, Wilfried; Beretvas, S. Natasha; Moeyaert, Mariola; Ferron, John M.; Van den Noortgate, Wim (Behavior research methods, 2020)
The MultiSCED web application has been developed to assist applied researchers in behavioral sciences to apply multilevel modeling to quantitatively summarize single-case experimental design (SCED) studies through a user-friendly point-and-click interface embedded within R. In this paper, we offer a brief introduction to the application, explaining how to define and estimate the relevant multilevel models and how to interpret the results numerically and graphically. The use of the application is illustrated through a re-analysis of an existing meta-analytic dataset. By guiding applied researchers through MultiSCED, we aim to make use of the multilevel modeling technique for combining SCED data across cases and across studies more comprehensible and accessible.